Changes in the electro-physical properties of MCT epitaxial films affected by a plasma volume discharge induced by an avalanche beam in atmospheric-pressure air. (October 2015) - Grigoryev, D V; Voitsekhovskii, A V; Lozovoy, K A; Tarasenko, V F; Shulepov, M A
Abstract: In this paper the influence of the plasma volume discharge of nanosecond duration formed in a non-uniform electric field at atmospheric pressure on samples of epitaxial films HgCdTe (MCT) films are discussed. The experimental data show that the action of pulses of nanosecond volume discharge in air at atmospheric pressure leads to changes in the electrophysical properties of MCT epitaxial films due to formation of a near-surface high- conductivity layer of the n-type conduction. The preliminary results show that it is possible to use such actions in the development of technologies for the controlled change of the properties of MCT.